Past Adversity Influencing Now (PAIN): perspectives on the impact of temporal language on the persistence of pain - Hudson, Matt; Johnson, Mark I. (Frontiers in Pain Research, 2023)
Persistent pain is a significant healthcare issue, often unresponsive to traditional treatments. We argue for incorporating non-biomedical perspectives in understanding pain, promoting more comprehensive solutions. This article explores how language, specifically time-related terms, may affect the persistence (stickiness) of pain. We delve into how language influences one's experience of the world, especially in understanding pain through spatial metaphors. Notably, time perceptions differ across languages and cultures and there is no absolute construct of temporal pain experience. In English, time is viewed linearly as past, present, and future. We introduce a framework called Past Adversity Influencing Now (PAIN) which includes various temporal phases of pain; Past Perfect, Past Imperfect, Present, Future Imperfect, and Future Perfect. We suggest that past negative memories (emotional memory images) can “trap” individuals in a “sticky” pain state. We speculate that the process of diagnosing pain as “chronic” may solidify this “stickiness”, drawing from the ancient Greek idea of “logos”, where pain communicates a message across time and space needing recognition. Our PAIN framework encourages examining pain through a temporal lens, guiding individuals towards a more positive future.